Clinical and experimental role of ring finger protein 180 on lymph node metastasis and survival in gastric cancer. Issue 4 (25th January 2016) - Deng, J.; Liang, H.; Zhang, R.; Hou, Y.; Liu, Y.; Ying, G.; Pan, Y.; Hao, X.
Abstract: Background: The hypermethylation of ring finger protein (RNF) 180 DNA promoter is significantly associated with lymph node metastasis of gastric cancer. The present study explored the potential mechanism of RNF180‐regulated lymph node metastasis of gastric cancer. Methods: Associations between clinicopathological and survival data and RNF180 expression in gastric cancer tissues were analysed. The effects of RNF180 re‐expression on gastric cancer cells were determined by means of proliferation, invasion, growth and lymphangiogenesis assays. A genome microarray was used to find potential target genes associated with lymphatic metastasis of gastric cancer cells regulated by RNF180. Results: RNF180 was silenced or downregulated in 99 (73·9 per cent) of 134 gastric cancer tissues compared with 41·8 per cent of paired non‐tumour tissues from patients. As an independent prognostic indicator of gastric cancer, RNF180 expression in gastric cancer tissues was negatively related to the number of metastatic lymph nodes. RNF180 was also downregulated in all seven gastric cancer cell lines examined. The re‐expression of RNF180 in gastric cancer cells inhibited colony formation, proliferation, migration and invasion in vitro ; re‐expression of RNF180 also suppressed tumour growth and lymphangiogenesis in mice. Furthermore, re‐expression of RNF180 downregulated the expression of hepatocyte growth factor, matrix metalloproteinase (MMP) 2, MMP‐14, vascular endothelial growth factor C/D and chemokine receptor 7 in gastric cancer cells; it also downregulated the expression of podoplanin in tumour tissue of nude mice. Conclusion: RNF180 appears to act as a suppressor gene that inhibits lymph node metastasis in gastric cancer. Surgical relevance Biological mechanisms that lead to lymph node metastasis in gastric cancer have not been clarified. Ring finger protein (RNF) 180 has been shown to participate in the processes of lymph node metastasis in several human malignancies. In this study, silencing or downregulation of RNF180 expression was significantly associated with lymph node metastasis of gastric cancer. In vitro, RNF180 expression suppressed the common biological characteristics of gastric cancer cells (HGC‐27), including proliferation, invasion, lymphangio genesis and chemotaxis. RNF180 expression also inhibited tumour growth and tumour lymphangiogenesis in vivo . These results show that RNF180 is capable of inhibiting lymph node metastasis of gastric cancer by suppressing the intracellular activation of malignant molecular signals. Therefore, RNF180 could be considered as a promising biomarker for evaluation of the tumour aggressiveness and may be a target for future therapeutic intervention. Abstract : Possible new therapeutic target